Manual differential count and automated differential leukocyte count in normal individuals: a comparative study - Bajimaya, Mahesh Man; Mahotra, Narayan Bahadur; Shrestha, Lava; Pradhan, Sait; Malla, Neha; Kandel, Sabita; Chaudhary, Sonam; Gurung, Sanyukta (Journal of Physiological Society of Nepal, 2021)
Introduction: Differential leukocyte is a frequently ordered laboratory test. It is the percentage distribution of types of leukocytes on a stained film. There are two methods to determine differential leukocyte count which are manual and automated. Manual method is considered the gold standard and is used to validate differential counts obtained by automated method. The comparative knowledge about the different methods to determine differential leukocyte count may guide us to use of proper method to determine the differential count more accurately and in a shorter time. The study aims to compare differential leukocyte count of normal blood samples by manual and automatic methods. Materials and methods: A cross-sectional, analytical study was conducted in laboratory of Kasturba Hospital, Manipal. A total of 347 blood samples of adults that did not show abnormalities in automatic analyzer were included in the study by purposive sampling method. Blood smears for manual count were prepared by Leishman’s stain. Results: A significant difference was observed between manual and automated leukocyte differential counts in 100 and 200 cells per specimen in neutrophils, lymphocytes, monocytes, eosinophils and basophils. Conclusions: The study concludes the need of improving accuracy and reliability of the automated methods. A reference range generated by further studies could help provide more accurate determination of differential leukocyte count.